Machinery Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - University of Washington Libraries. Special Collections Division (1909)
This photograph was taken by one of the many amateur photographers allowed to photograph the grounds, buildings and exhibits of the Alaska-Yukon-Pacific-Exposition. By purchasing a day pass, an amateur photographer with a camera smaller then 6" x 8" was allowed to take unlimited pictures inside the exposition. PH Coll 756.12 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number